2016
DOI: 10.3892/ol.2016.5148
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses colon cancer cell invasion via AMPK-induced inhibition of NF–κB, uPA activator and MMP9

Abstract: Abstract. Curcumin, an active nontoxic ingredient of turmeric, possesses potent anti-inflammatory, antioxidant and anti-cancer properties; however, the molecular mechanisms of curcumin are not fully understood. The transcription factor nuclear factor-κB (NF-κB) is key in cellular processes, and the expression/activation of urokinase-type plasminogen activator (uPA) and matrix metalloproteinase-9 (MMP9) are crucial for cell invasion. The present study investigated the hypothesis that curcumin inhibits colon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 52 publications
5
61
1
Order By: Relevance
“…NF‐κB inhibitors, which are known to regulate the NF‐κB activation stabilized by protease inhibitors, could also induce apoptosis in the human leukemia cells . A previous study has done well to demonstrate that the NF‐κB inhibitor can suppress colon cancer cell invasion through the inhibition of NF‐κB . Furthermore, our study demonstrated thoroughly that the NF‐κB inhibitor suppressed the expressions of TLR4 and NF‐κB in the serum.…”
Section: Discussionsupporting
confidence: 69%
“…NF‐κB inhibitors, which are known to regulate the NF‐κB activation stabilized by protease inhibitors, could also induce apoptosis in the human leukemia cells . A previous study has done well to demonstrate that the NF‐κB inhibitor can suppress colon cancer cell invasion through the inhibition of NF‐κB . Furthermore, our study demonstrated thoroughly that the NF‐κB inhibitor suppressed the expressions of TLR4 and NF‐κB in the serum.…”
Section: Discussionsupporting
confidence: 69%
“…Kubota et al () reported dietary curcumin feeding significantly activated AMP‐activated kinase, decreased the expression of COX‐2 protein, and inhibited NF‐ κ B activity on the colonic mucosa of AOM‐ treated mice. In recent study investigation has shown that the anti‐metastatic effect of curcumin in CRC cell lines (LoVo and SW480) via AMPK activation and following inhibition of p65 NF‐κB, MMP9 and uPA (Tong, Wang, Sun, & Suo, ). Curcumin could significantly inhibited tumor growth and metastasis in mouse model of colorectal peritoneal carcinomatosis (CRPC).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin exerts an anti-inflammatory effect and protects cardiomyocytes against high glucose-induced apoptosis through this pathway (9,52). Additionally, previous studies demonstrated that the Wnt/β-catenin, Notch-1, nuclear factor-κB and mitogen-activated protein kinase signaling pathways were also involved in the effects of curcumin in cancer cells (51,(53)(54)(55)(56)(57), and these signaling pathways may also be involved in the growth-inhibitory effect of curcumin in LCSCs; however, this requires further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%